The Linguistic Construction of Social Categories in Toddlers. Issue 1 (27th May 2013) - Diesendruck, Gil; Deblinger‐Tangi, Ronit
<x xml:space="preserve">Abstract</x> Kindergarteners treat certain social categories as natural kinds. This study addressed how children pick out social categories. Ninety‐one 19‐ and 26‐month‐olds were familiarized to exemplars of categories of people (e.g., Blacks–Whites, men–women) and animals (e.g., cows–horses). Participants then saw a picture matching the familiarization category and another that did not, and were asked to select which was like the familiarization pictures. For half of the participants, a label was attached to familiarization exemplars, while for the other half, no label was mentioned. The main finding was that for the younger toddlers, labels significantly improved recognition of the categories of people, but not of animals. These results are taken to support the notion that social categories are indeed culturally constructed.